Residências de medicina de família e comunidade de Palmas - Tocantins: uma análise do perfil, atuação no mercado de trabalho e formação dos seus egressos - Cavalcante, Gecilda Régia Ramalho Vale (2019)
Family and Community Medicine (MFC) is the medical specialty recognized for offering the best standards of healthcare to the general population, based on the principles of Primary Health Care (PHC). Under this perspective, Palmas- TO has created its MFC residency programs from the year of 2012. This research aimed to characterize the profile and overall perception of the graduates from the Residencies of Family and Community Medicine (RMFC) of the Palmas School of Public Health Foundation (FESP) and the Federal University of Tocantins (UFT). This is an exploratory, descriptive and cross-sectional study with a mixed approach. In order to conduct this study, a questionnaire with closed and open questions was proposed to the 31 graduates who had completed the RMFC program by 2018. The results are presented in two articles. First, a quantitative approach held descriptive and inferential analysis of the data using the Chi-square Pearson test, with a level of significance of 5%. About 77.4% (n = 24) of respondents were female and 51.6% (n = 16) were under 30 years old. Most of them were currently working in Palmas – TO (51.8%, n = 18). The main contributions of the RMFC training were the improvement in the organization and safety of the egress’s work process (32.5%, n = 10), acquired through the learning of the PHC attributes, as well as humanization and personal development (32.5%, n = 10). All participants stated that it is essential to attend the RMFC program in order to practice in PHC, as well as signalled that the training contributed to their growing as distinctive professionals, regardless of their current field of activity. The main motivations for the specialty choice were the improvement of their knowledge in the expanded clinic (33.3%, n = 4), as well as the acquisition of a 10% bonus in another residency program contest. Dissatisfaction was related to professional devaluation and low remuneration (75%, n = 12). Preceptorship exercise was significantly related (p = 0.001) to the graduates who remained in the CFM area. The program was mostly evaluated as good or excellent (93.6%, n = 29). For the second article, with a qualitative approach, the answers were analysed and interpreted based on Bardin's Thematic Content Analysis technique and the results constituted four empirical categories: The training in CFM in the Graduate’s Work Process, Recognition and Application PHC attributes, MFC Training Powers and MFC Challenges. The qualitative data indicated that the Palmas-TO CFM Residency Programs contributed to the professional practice and the profile shaping of their graduates through the strengthening and effectiveness of PHC attributes, which surpassed the practice of the specialty. RMFC Palmas - TO contributes not only to the increase in the provision of qualified professionals for MFC in the state, but also to the improvement of the technical quality and personal development of its graduates, which are built through the strengthening of the PHC principles in their daily professional practices.